2010
DOI: 10.1051/forest/2009131
|View full text |Cite
|
Sign up to set email alerts
|

Allométrie du bois de cœur et de l’aubier pour sept espèces d’arbres tempérées chinoises

Abstract: Abstract• Allometry of sapwood/heartwood is essential for understanding tree growth, water transport and carbon allocation, timber production and use, but such an allometry is lacking for Chinese temperate tree species.• We studied the allometry and development of heartwood and sapwood for seven Chinese temperate tree species: Korean pine (Pinus koraiensis Sieb. et Zucc), Dahurian larch (Larix gmelinii Rupr.), Japanese elm (Ulmus davidiana Planch var. japonica (Rehd.) Nakai), Manchurian ash (Fraxinus mandshuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
(50 reference statements)
2
14
0
1
Order By: Relevance
“…In the present study, diameter at breast height (DBH) had the highest correlation with heartwood radius, area and volume among the four tree growth factors tested (DBH, tree height, height to crown base, and crown width), and the fitted heartwood volume model based on DBH could predict accurately for T. grandis trees of different social status. The findings were in accordance with Fernandez-Solis's [12] study on T. grandis and Wang's [33] study on several temperate tree species, where DBH was also demonstrated as the most commonly used and the most effective variable for estimating heartwood volume.…”
Section: Relationship Between Tree Growth and Heartwood And Sapwood Asupporting
confidence: 89%
“…In the present study, diameter at breast height (DBH) had the highest correlation with heartwood radius, area and volume among the four tree growth factors tested (DBH, tree height, height to crown base, and crown width), and the fitted heartwood volume model based on DBH could predict accurately for T. grandis trees of different social status. The findings were in accordance with Fernandez-Solis's [12] study on T. grandis and Wang's [33] study on several temperate tree species, where DBH was also demonstrated as the most commonly used and the most effective variable for estimating heartwood volume.…”
Section: Relationship Between Tree Growth and Heartwood And Sapwood Asupporting
confidence: 89%
“…other angiosperm species [13,14]). This feature differs significantly from the considered conifers, which have a wider proportion of sapwood [61,62] (cf. also observation of the last ring accounting for only 15%-20% of the hydraulic conductivity of Scots pine [63]), whereas birch does not form a heartwood at all.…”
Section: Climatic Response and Growth Modeling Of Treesmentioning
confidence: 59%
“…Moore et al (2008) reported that annual stem diameter increment explained 42-74% of the variation in E S for P. taeda. Wang et al (2010) reported that sapwood area and sapwood width were positively correlated with DBH of seven tree species. In addition, larger stems have larger root systems and could potentially transport more CO 2 from their root systems upwards in the xylem into the main stem Aubrey and Teskey 2009).…”
Section: Discussionmentioning
confidence: 99%